2006
DOI: 10.1002/anie.200602206
|View full text |Cite
|
Sign up to set email alerts
|

Anion‐Templated Syntheses of Pseudopeptidic Macrocycles

Abstract: A very welcome guest: The terephthalate anion efficiently templates the selective assembly of a tetraimino dianion host–guest complex, which can be reduced to the final [2+2] pseudopeptidic macrocycle (see scheme; O red, blue N).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 82 publications
(33 citation statements)
references
References 53 publications
0
33
0
Order By: Relevance
“…In this context, pseudopeptidic compounds are good receptors of anions due to the coordination properties of the amide groups [2,3]. For this purpose, the preorganization provided by macrocyclic structures is important, and the preparation of such structures from C 2 pseudopeptidic bis(amidoamines) has been investigated in detail in our research group [4][5][6][7]. Previous studies focused on compounds such as 1 (Scheme 1) [4].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, pseudopeptidic compounds are good receptors of anions due to the coordination properties of the amide groups [2,3]. For this purpose, the preorganization provided by macrocyclic structures is important, and the preparation of such structures from C 2 pseudopeptidic bis(amidoamines) has been investigated in detail in our research group [4][5][6][7]. Previous studies focused on compounds such as 1 (Scheme 1) [4].…”
Section: Introductionmentioning
confidence: 99%
“…templates, as typically described in the synthesis of large macrocycles. [45,47] It has been demonstrated that a combination of solvophobic effects and the occurrence of preorganization of the intermediates, assisted by intramolecular hydrogen-bonding, explain such good yields. [40] The open-chain derivatives were synthesized in a similar way but by using the corresponding alkaneamines (Scheme 3).…”
Section: Synthesismentioning
confidence: 99%
“…[40][41][42][43][44][45] The probes are of three types: Macrocyclic bis-aminoamides 1-7, openchain bis-aminoamides 8 and 9, and mono-aminoamides 10-12. As can be seen in Scheme 1, the differences between these compounds comprise slight variations in the chemical nature of the building blocks employed for their synthesis, such that either valine or phenylglycine have been used as well as different polymethylene bridges with n = 2, 3, 4, 5, 6 or 8 units.…”
Section: Synthesismentioning
confidence: 99%
“…Pseudopeptidic macrocycles bearing both amine and amide functional groups have been also reported by Luis et al [57][58][59][60][61][62] The key step for the synthesis of these compounds is the macrocyclization reaction, which is favored by the fold- . (13).…”
Section: Macrocyclic Receptorsmentioning
confidence: 99%
“…Taking advantage of the amide-anion strong interaction, we envisioned to use an anion to produce the necessary preorganization in the case of the more flexible derivatives (49a,b) [62]. Taking advantage of the amide-anion strong interaction, we envisioned to use an anion to produce the necessary preorganization in the case of the more flexible derivatives (49a,b) [62].…”
Section: Macrocyclic Receptorsmentioning
confidence: 99%